Spoken Word Recognition Using MFCC and Learning Vector Quantization - Esmeralda C. Djamal; Neneng Nurhamidah; Ridwan Ilyas (IAES Indonesia Section, 2017)
Identification of spoken word(s) can be used to control external device. This research was result word identification in speech using Mel-Frequency Cepstrum Coefficients (MFCC) and Learning Vector Quantization (LVQ). The output of system operated the computer in certain genre song appropriate with the identified word. Identification was divided into three classes contain words such as